Expansion of two-dimensional imaging apertures for resolutionimprovement in long-wavelength holography - Abdel-Aal, R.E. (1990)
A method is described for improving resolution in long-wavelength holography by expanding the two-dimensional hologram aperture. Simulation results are presented to illustrate resolution improvements obtained when doubling the linear size of square apertures for imaging single-point, multiple-point and quasi-continuous objects in the presence of noise. A technique for improving the quality of images reconstructed from predicted holograms using a number of focus measures is described. Alternative strategies for reconstructing the two-dimensional holograms are discussed and their performance compared regarding prediction errors and noise. Data is supplied on CPU time usage for hologram expansion and reconstruction on a VAX-11/785 computer